2021
DOI: 10.1080/02723638.2021.1878439
|View full text |Cite
|
Sign up to set email alerts
|

Charting the design and implementation of the smart city: the case of citizen-centric bikeshare in Hamilton, Ontario

Abstract: Previous scholarship on the smart city has expressed concern at the top-down, technocratic nature of smart technologies and the lack of meaningful citizen participation in their development. In this paper, we utilize instrumentalization theory to trace the initiation, design and deployment of a specific smart city initiative: bikeshare in Hamilton, Ontario. Smart bikeshare is increasingly seen as complicit in processes of social stratification, serving a predominately white, middle-class demographic and partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…GBFS data have also been used by several bikesharing studies (2,23,(31)(32)(33)(34)(35). In these studies, GBFS data has shown advantages in its large sample sizes and accurate spatiotemporal information compared with the survey data.…”
Section: Bikesharing Studies and Corresponding Datasetmentioning
confidence: 99%
“…GBFS data have also been used by several bikesharing studies (2,23,(31)(32)(33)(34)(35). In these studies, GBFS data has shown advantages in its large sample sizes and accurate spatiotemporal information compared with the survey data.…”
Section: Bikesharing Studies and Corresponding Datasetmentioning
confidence: 99%